2020
DOI: 10.1038/s41598-020-74383-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurement of shear modulus of the human cornea using optical coherence elastography

Abstract: Corneal stiffness plays a critical role in shaping the cornea with respect to intraocular pressure and physical interventions. However, it remains difficult to measure the mechanical properties noninvasively. Here, we report the first measurement of shear modulus in human corneas in vivo using optical coherence elastography (OCE) based on surface elastic waves. In a pilot study of 12 healthy subjects aged between 25 and 67, the Rayleigh-wave speed was 7.86 ± 0.75 m/s, corresponding to a shear modulus of 72 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 37 publications
2
70
0
Order By: Relevance
“…These observations led us to propose that our eye phantoms could be utilized to investigate deformation of the eye caused by IOP change or to measure the tension from the outside of the eyeball. Indeed, a recent study on biomechanics of an in vivo human cornea showed that the corneal shear modulus was independent of both CCT as well as IOP 17 .…”
Section: Discussionmentioning
confidence: 99%
“…These observations led us to propose that our eye phantoms could be utilized to investigate deformation of the eye caused by IOP change or to measure the tension from the outside of the eyeball. Indeed, a recent study on biomechanics of an in vivo human cornea showed that the corneal shear modulus was independent of both CCT as well as IOP 17 .…”
Section: Discussionmentioning
confidence: 99%
“…OCE (compression, ARF based, and shear wave.) is extensively used to assess the viscoelastic properties of the human cornea in vivo as the superior submicron scale resolution of OCT can capture subtle changes in wave properties [153] and tissue properties, making it suitable for the detection of early-onset disease such as keratoconus [154]. In addition, in vivo dynamic OCE has been performed on human skin to assess its mechanical properties [155].…”
Section: Adult Tissuementioning
confidence: 99%
“…Optical coherence elastography (OCE) was developed by combining a loading system to exert a sample stimulation force and an optical coherence tomography (OCT) system to observe the resulting tissue displacements (strains) or mechanical waves ( Schmitt, 1998 ). OCT/OCE provides micrometer-scale axial and lateral resolutions, and the use of phase-sensitive OCT detection ( Zhao et al, 2000 ; Kirkpatrick et al, 2006 ) can further enhance the dynamic elastography detection sensitivity to a sub-nanometer scale ( Lan et al, 2017 ), making it possible to detect minute-magnitude dynamics for in vivo human corneas ( Lan et al, 2020a ; Ramier et al, 2020 ; Lan et al, 2021b ). The measurement of tissue biomechanics typically centers on Young’s modulus, a representation of elasticity expressed as the slope between the force (stress) and the resulting fractional deformation (strain).…”
Section: Introductionmentioning
confidence: 99%